2016
DOI: 10.1016/j.desal.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of combined adsorption desalination and cooling cycles with integrated evaporator/condenser

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In their work, a comparison between the AQSOA-ZO2 and silica-gel has been performed when operating in a two bed adsorption cycle for the production of desalinated water and cooling. Youssef et al [16], have investigated the use of AQSOA-Z02 in a novel adsorption system consisting of evaporator, condenser, integrated evaporator-condenser device and 4 adsorber beds. Results showed that by utilizing heat recovery between system components, water production can reach 12.4 m 3 /tonne adsorbent/day and cooling of 32.4 Rton/tonne adsorbent at evaporator inlet water temperature of 10 o C.…”
Section: Nomenclature C Pmentioning
confidence: 99%
“…In their work, a comparison between the AQSOA-ZO2 and silica-gel has been performed when operating in a two bed adsorption cycle for the production of desalinated water and cooling. Youssef et al [16], have investigated the use of AQSOA-Z02 in a novel adsorption system consisting of evaporator, condenser, integrated evaporator-condenser device and 4 adsorber beds. Results showed that by utilizing heat recovery between system components, water production can reach 12.4 m 3 /tonne adsorbent/day and cooling of 32.4 Rton/tonne adsorbent at evaporator inlet water temperature of 10 o C.…”
Section: Nomenclature C Pmentioning
confidence: 99%
“…Recent papers illustrate adsorption materials and adsorption cooling system configurations and their combination with other cooling and desalination systems 19‐21 . The researchers continued to find new sorbent materials with high adsorption capacities like a new MOF, clays, aluminum fumarate, and copper sulfate 22‐30 or improve the existing materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recent papers illustrate adsorption materials F I G U R E 1 Adsorption systems: (A) adsorption desalinationcooling, (B) adsorption desalination with heat recovery (condenser/ evaporator), (C) adsorption cooling system and adsorption cooling system configurations and their combination with other cooling and desalination systems. [19][20][21] The researchers continued to find new sorbent materials with high adsorption capacities like a new MOF, clays, aluminum fumarate, and copper sulfate [22][23][24][25][26][27][28][29][30] or improve the existing materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable number of studies have been conducted on adsorbents such as silica gel and zeolite [16,17,[27][28][29]. Unfortunately, the regenerating temperatures are usually >60 C [30,31] which are not always available. Therefore, it is desirable to find alternative adsorbents which can efficiently process large amounts of water with low regenerating temperatures [32].…”
Section: Introductionmentioning
confidence: 99%